2009
DOI: 10.1002/job.650
|View full text |Cite
|
Sign up to set email alerts
|

Transformational and transactional leadership and innovative behavior: The moderating role of psychological empowerment

Abstract: SummaryInnovative behavior is increasingly important for organizations' survival. Transformational leadership, in contrast to transactional leadership, has been argued to be particularly effective in engendering follower innovative behavior. However, empirical evidence for this relationship is scarce and inconsistent. Addressing this issue, we propose that follower psychological empowerment moderates the relationship of transformational and transactional leadership with follower innovative behavior. In a field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
631
3
64

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 728 publications
(733 citation statements)
references
References 66 publications
35
631
3
64
Order By: Relevance
“…Transformational leadership assumed to be a major determinant for innovation,Burns,(1978) described transformational leadership as a type of leadership that raises followers morality and motivation by four dimensions : Idealized influence, intellectual simulation, inspirational motivation, and individual consideration .But how Transformational leadership may affect innovation (Pieterse,A,et al,2010) and Engelen et al, (2014) illustrated that the effect of each dimension of transformational leadership may have a different influence on the organizational innovation.…”
Section: Introductionmentioning
confidence: 99%
“…Transformational leadership assumed to be a major determinant for innovation,Burns,(1978) described transformational leadership as a type of leadership that raises followers morality and motivation by four dimensions : Idealized influence, intellectual simulation, inspirational motivation, and individual consideration .But how Transformational leadership may affect innovation (Pieterse,A,et al,2010) and Engelen et al, (2014) illustrated that the effect of each dimension of transformational leadership may have a different influence on the organizational innovation.…”
Section: Introductionmentioning
confidence: 99%
“…To this point, previous studies have mainly identified how leadership influence individual innovativeness (e.g., Zhang and Bartol, 2010 [42]; Pieterse, Van Knippenberg, Schippers and Stam, 2010 [44]) and most of these studies focused on testing the linear relationship between positive leadership and individual innovativeness. It is worth noting that few previous studies have tested different effects of specific leadership skills on subordinate innovativeness.…”
Section: Research Implicationsmentioning
confidence: 99%
“…По-мимо улучшения исполнения своих основ-ных рабочих задач, работник демонстриру-ет позитивные установки по отношению к работе и организации -удовлетворенность работой [Brandt, Laiho, 2013;Braun et al, 2013] и приверженность организации [Avolio et al, 2004, Simosi, Xenikou, 2010Kara, 2012], готовность к организационным из-менениям [Bommer, Rich, Rubin, 2005]. Трансформационный стиль руководителя стимулирует надролевое («гражданское» и инновационное) поведение подчиненных [Whit tington, Goodwin, Murray, 2004;Boerner, Eisenbeiss, Griesse, 2007;Gumusluoglu, Ilsev, 2009;Pieterse et al, 2010;Grant, 2012;López-Domínguez, Simo, Enache, 2013]. По вы ша ет ся их внутренняя, содер-жательная мотивация к работе [Piccolo, Colquitt, 2006], усиливается вовлеченность в работу (work engagement) [Schaufeli, Salanova, 2007].…”
Section: трансформационное лидерство: концепция и эмпирические исследunclassified